PROXY SERVER SEBAGAI WEB FILTERING - Widanto, Frantina Andri; Riana, Dwiza (Jurnal Pilar Nusa Mandiri, 2007)
A proxy server is a kind of buffer between your computer and the Inter-net resources you are accessing. They accumulate and save files that are most often requested by thousands of Internet users in a special database. Therefore, proxy servers are able to increase the speed of your connection to the Internet. A proxy server may already contain information you need by the time of your re-quest, making it possible for the proxy to deliver it immediately. The overall in-crease in performance may be very high. Also, proxy servers can help in cases when they want to filter any web resource users access like a web full violent , pomografi, hacking or cracking. This research give a way to buffer between us-ers computer and the Internet resources users are accessing with sguid applica-tion with GNU/Linux base. Proxy server with application Squid is a Internet gate-way to accessing Internet for server GNU/Linux base with client that using win-dows XP base.